Full-disc 13CO(1–0) mapping across nearby galaxies of the EMPIRE survey and the CO-to-H2 conversion factor. Issue 3 (9th January 2018) - Cormier, D; Bigiel, F; Jiménez-Donaire, M J; Leroy, A K; Gallagher, M; Usero, A; Sandstrom, K; Bolatto, A; Hughes, A; Kramer, C; Krumholz, M R; Meier, D S; et al.
Abstract: Carbon monoxide (CO) provides crucial information about the molecular gas properties of galaxies. While 12 CO has been targeted extensively, isotopologues such as 13 CO have the advantage of being less optically thick and observations have recently become accessible across full galaxy discs. We present a comprehensive new data set of 13 CO(1–0) observations with the IRAM 30-m telescope of the full discs of nine nearby spiral galaxies from the EMPIRE survey at a spatial resolution of ∼1.5 kpc. 13 CO(1–0) is mapped out to 0.7 − 1  r 25 and detected at high signal-to-noise ratio throughout our maps. We analyse the 12 CO(1–0)-to- 13 CO(1–0) ratio (ℜ) as a function of galactocentric radius and other parameters such as the 12 CO(2–1)-to- 12 CO(1–0) intensity ratio, the 70-to-160 μm flux density ratio, the star formation rate surface density, the star formation efficiency, and the CO-to-H2 conversion factor. We find that ℜ varies by a factor of 2 at most within and amongst galaxies, with a median value of 11 and larger variations in the galaxy centres than in the discs. We argue that optical depth effects, most likely due to changes in the mixture of diffuse/dense gas, are favoured explanations for the observed ℜ variations, while abundance changes may also be at play. We calculate a spatially resolved 13 CO(1–0)-to-H2 conversion factor and find an average value of 1.0 × 10 21  cm −2  (K km s −1 ) −1 over our sample with a standard deviation of a factor of 2. We find that 13 CO(1–0) does not appear to be a good predictor of the bulk molecular gas mass in normal galaxy discs due to the presence of a large diffuse phase, but it may be a better tracer of the mass than 12 CO(1–0) in the galaxy centres where the fraction of dense gas is larger.